Cultivation of Multicultural Values at Karuna Dipa Junior High School in Palu - Maolana (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
This research aims to examine how SMP Karuna Dipa Palu cultivates multicultural values, fostering coexistence and respect among students from diverse cultures, tribes, ethnicities, and religions. This research is a type of field study that combines descriptive qualitative methods. This research employs a case study approach. The data collection techniques used in this research are interviews, observations, and documentation studies. The results show that the values of equality, justice, tolerance, and deliberation are the main focus, although nine are taught. The intracurricular and extracurricular activities apply the strategy of value inculcation through material integration, knowledge formation, prejudice reduction, and equality pedagogy. The school climate and the active role of educators serve as supportive factors, while differences in student abilities and the lack of visual media pose barriers. In conclusion, to maximize the implementation of multicultural values, schools are advised to complete supporting facilities, expand the application of values in all subjects, and increase socialization among educators.